The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1111/tbed.12886
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and molecular characterization of chicken anaemia virus from commercial and native chickens in Taiwan

Abstract: Chicken infectious anaemia (CIA) is a disease with a highly economic impact in the poultry industry. The infected chickens are characterized by aplastic anaemia and extreme immunosuppression, followed by the increased susceptibility to secondary infectious pathogens and suboptimal immune responses for vaccination. Commercially available CIA vaccines are routinely used in the breeders in Taiwan to protect their progeny with maternal-derived antibodies. However, CIA cases still occur in the field and little is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…In order to verify the division into these genogroups, a phylogenetic analysis including the 11 complete VP1 sequences obtained and the reference sequences available on GenBank was performed and confirmed the Italian strains classification with bootstrap values > 70 (Figure 3). CIAV strains are classified into genogroups I, II, IIIa and IIIb [18] and IV [19], and the Italian strains analyzed in the present study belonged to genogroups II (n.10 strains), IIIa (n.11 strains) or IIIb (n.4 strains). Noticeably, the CIAV/IT/CK/1153-1/19 strain clustered with the vaccine strain 26P4, and strains CIAV/IT/CK/1155/19, CIAV/IT/CK/1180/19 and CIAV/IT/CK/1195/19 with the Del-Ros vaccine strain, both in genogroup IIIb.…”
Section: Phylogenetic Analysismentioning
confidence: 84%
See 2 more Smart Citations
“…In order to verify the division into these genogroups, a phylogenetic analysis including the 11 complete VP1 sequences obtained and the reference sequences available on GenBank was performed and confirmed the Italian strains classification with bootstrap values > 70 (Figure 3). CIAV strains are classified into genogroups I, II, IIIa and IIIb [18] and IV [19], and the Italian strains analyzed in the present study belonged to genogroups II (n.10 strains), IIIa (n.11 strains) or IIIb (n.4 strains). Noticeably, the CIAV/IT/CK/1153-1/19 strain clustered with the vaccine strain 26P4, and strains CIAV/IT/CK/1155/19, CIAV/IT/CK/1180/19 and CIAV/IT/CK/1195/19 with the Del-Ros vaccine strain, both in genogroup IIIb.…”
Section: Phylogenetic Analysismentioning
confidence: 84%
“…The patterns of amino acid substitutions in specific amino acid sites, located at positions 22, 75, 97, 125, 139, 144, 157, 287, 290, 370, 394 and 413 of the VP1 protein, are reported in Table 4. These amino acids showed variability among CIAV isolates [19,21,35,41], and changes in some of them are associated with viral attenuation [11][12][13][42][43][44]. The full genome sequencing allowed us to analyze VP2 and VP3 genetic variability among the detected strains, and in comparison with other strain sequences retrieved from GenBank.…”
Section: Sequence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal immunity usually disappears by approximately 3 weeks of age. A high prevalence of CIA was detected in older chickens of layer and broiler breeds in Taiwan [7]. The detected cases were naturally occurring horizontal infections with CAV, which most likely occurred by exposure to CAV in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…McNulty et al [5] demonstrated that the minimum dose of CAV that caused anemia in a high proportion of 1-day-old inoculated chickens was above 10 3 .3 50% tissue culture infectious dose (TCID 50 ). In Taiwan, most field CAV cases were detected in older chickens with transient poor performance [6]. Dren et al [7] examined the pathogenesis of CAV infection in 6-week-old chickens with different inoculation doses.…”
Section: Introductionmentioning
confidence: 99%